Characterization of cardiac bradyarrhythmia associated with LGI1-IgG autoimmune encephalitis - Zhao-Fleming, Hannah H.; Zahid, Anza; Lu, Tong; Sun, Xiaojing; Pittock, Sean J.; Lee, Hon-Chi; Dubey, Divyanshu (Frontiers in Immunology, 2022)
Objective To evaluate and characterize cardiac arrythmias associated with LGI1-IgG (Leucine-rich glioma inactivated 1–IgG) autoimmune encephalitis (AE). Patients and methods In this retrospective descriptive study, we identified Mayo Clinic patients (May 1, 2008 – December 31, 2020) with LGI1-IgG AE who had electrocardiogram proven bradyarrhythmias during the initial presentation. Inclusion criteria were 1) LGI1-IgG positivity with a consistent clinical syndrome; 2) electrocardiographic evidence of bradyarrhythmia; and 3) sufficient clinical details. We excluded patients who were taking negative ionotropic agents at the time of their bradyarrhythmias. We collected demographic/clinical data including details of bradyarrhythmia (severity, duration, treatments), and neurologic and cardiac outcomes. Results We found that patients with LGI1-IgG AE had bradyarrhythmia at a frequency of 8% during the initial presentation. The bradyarrhythmia was often asymptomatic (6/11, 55%); however, the episode was severe with one patient requiring a pacemaker. Outcome was also generally favorable with the majority (8/11, 73%) having full resolution without further cardiac intervention. Lastly, we found that mouse and human cardiac tissues express LGI1 (mRNA and protein). Conclusion LGI1-IgG AE can be rarely associated with bradyarrhythmias. Although the disease course is mostly favorable, some cases may require pacemaker placement to avoid devastating outcomes.